'Nothing will ever be the same again'. Personal commitment and political subjectivation in the 20 February Movement in Morocco. Issue 2 (4th March 2021) - Vacchiano, Francesco; Afailal, Hafsa
ABSTRACT: Based on an analysis of the stories of engagement of young activists who took part in the 20 February Movement in Morocco, this contribution explores the process of individual transformation that occurred during the experience of activism. We use the concept of political subjectivation to discuss the succession of moments of rupture and re-semanticisation, the new ethical configurations generated by the experience of activism and their long-term consequences. This contribution is part of an ethnographic study that has accompanied the evolution of the protests from 2011, carried out by the two authors first independently and, from 2017, within the framework of the 'Globally Sensitive: Revolt, Citizenship, and Expectations for the Future in North Africa' project.